The Application of Warm Acupuncture and Moxibustion and Midnight Noon Ebb Flow in the Diarra Dominant Irritable Bow Syndrome - Xu, Xujie; Lv, Shihan; Liu, Mingxing; Huang, Tingnan; Wang, Wenli (International Journal of Public Health and Medical Research, 2024)
This study aims to evaluate the efficacy and safety of warming acupuncture combined with the Ziwu Liuzhu method in D-IBS treatment and to investigate its potential mechanisms, including regulating gastrointestinal motility, neuro-immune networks, and gut microbiota balance. Methods: A randomized controlled trial was conducted with D-IBS patients who met diagnostic criteria, divided into three groups: warming acupuncture group, combined Ziwu Liuzhu and warming acupuncture group, and control group. The warming acupuncture group received warm needle stimulation at specific acupoints, while the combined group received treatments at specific times on Spleen and Stomach meridians according to the Ziwu Liuzhu method. Treatment outcomes were assessed using IBS symptom severity scores, quality of life scores, inflammatory marker analysis, and gut microbiota profiling. Results: The combined Ziwu Liuzhu and warming acupuncture group showed significant improvement in relieving diarrhea, abdominal pain, and bloating, with longer-lasting effects. This group also exhibited superior enhancement in gastrointestinal motility, neuro-immune function, and gut microbiota balance compared to the other groups. Additionally, the combined therapy demonstrated good safety, with no significant adverse effects observed.